Study of a pulse thermoelectric generator - Tan, Anthony Jian Sheng (Nanyang Technological University, 2024)
In this report, the main objective is to provide a better understanding of a pulsed thermoelectric generator with the calculated performance parameters in thermoelectric generator experiments conducted under pulsed heating condition and comparing it against steady state heating condition. The efficiency of the thermoelectric generator is also calculated for various cycle times and the waste heat inputs to the system itself which are quantified for formulations to understand the workings of a pulsed thermoelectric generator better. With the rising attention in clean sustainable development, the increase in energy efficiency is crucial for green energy conservations and considerations. The proposed pulsed thermoelectric generators can act as a heat harvesting system and the experimental results obtained from conducting useful experiments on the existing thermoelectric generator setup captured can help researchers understand the thermodynamic modelling as well as the simulation of an energy harvesting system better so that the implementation of this can be achieved in larger scales if possible. The section in the report allows deeper understanding of this study. A brief background introduction with the report’s objectives is laid out followed by detailed literature review of the theory of thermodynamic frameworks and past published works before conducting the experiments for this study. Several experiments are conducted like the open circuit voltage, calibration of rheostat, steady state heating and three pulsed heating experiments respectively with the formulations for data analysis for further discussions regarding the results obtained. The report ends off with conclusion and recommendations for future experiments that are relevant to this study.